Clinical Applications of Ultrasonography in the Shoulder and Elbow. Issue 9 (1st May 2018) - Lin, Albert; Gasbarro, Gregory; Sakr, Mark
Abstract : In the past 30 years, the use of ultrasonography in the field of orthopaedics has evolved. As ultrasonography has been refined, smaller machines with higher fidelity and better transducers have become available at a lower cost. Diagnostic and therapeutic applications of ultrasonography in the shoulder and elbow have expanded imaging options and provided alternatives to surgical management. Ultrasonography is a dynamic tool that affords immediate diagnostic assessment for clinical correlation and can be used for serial examinations and image guidance during therapeutic procedures. This imaging modality is highly reliable and accurate and may limit the need for costly imaging referrals, particularly in geographic areas where advanced imaging is not readily available. However, clinical expertise is paramount for ultrasonography, which is an operator-dependent modality. Ultrasonography is an effective educational resource; therefore, the curriculum in orthopaedic residency training programs should include education on this modality as the use of ultrasonography increases among orthopaedic surgeons.